2013
DOI: 10.1017/s0261444813000207
|View full text |Cite
|
Sign up to set email alerts
|

‘Effects of’ and ‘effects with’ captions: How exactly does watching a TV programme with same-language subtitles make a difference to language learners?

Abstract: Ever since Karen Price's ground-breaking work in 1983, we have known that same-language subtitles (captions) primarily intended for the deaf and hearing-impaired can provide access to foreign language films and TV programmes which would otherwise be virtually incomprehensible to non-native-speaker viewers. Since then, researchers have steadily built up our knowledge of how learners may make use of these when watching.The question remains, however, whether, and to what extent, watching subtitled programmes over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
67
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(71 citation statements)
references
References 38 publications
0
67
0
4
Order By: Relevance
“…Finally. captioned audiovisual input has the advantage that it also provides language learners with the written form of words, which might help learners decode the rapid speech of audiovisual input (Vanderplank, ). The present study adds to the growing body of evidence that captions are indeed useful for learning vocabulary.…”
Section: Discussionmentioning
confidence: 99%
“…Finally. captioned audiovisual input has the advantage that it also provides language learners with the written form of words, which might help learners decode the rapid speech of audiovisual input (Vanderplank, ). The present study adds to the growing body of evidence that captions are indeed useful for learning vocabulary.…”
Section: Discussionmentioning
confidence: 99%
“…They also point out that subtitles allow the integration of reading and listening skills, something that is invaluable for students studying in a second language. The work of Vanderplank (2013) in particular points to the benefits of subtitling in a context where students are confronted with challenging auditory input. He found that SLS increase comprehension particularly because they neutralise accents and dialects (a problem, for instance, in educational contexts such as higher education where many lecturers and speakers in supplementary videos have accents that may be unfamiliar to students), and also foregrounds unfamiliar phrases and words, such as new concepts and terminology as well as everyday expressions.…”
Section: Subtitles As Verbal Redundancy In Educational Videosmentioning
confidence: 99%
“…Further issues of "weak research design" (Vanderplank, 2013;p. 6) and reliance on pseudo-experimental approaches have limited the application of subtitling in educational contexts.…”
Section: Subtitles As Verbal Redundancy In Educational Videosmentioning
confidence: 99%
“…Generally learners only have the ability to use only or even just have the ability to watch it (Vanderplank, 2016). Although this is an ironic condition, almost all universities have weak student problems in information management.…”
Section: Introductionmentioning
confidence: 99%